Antecedents & Consequences of Online Apparel Purchases Among the Youth. Issue 1 (September 2020) - Somaiya, K. J.; Peter,
Abstract: Today's consumer buying behavior is very volatile and keeps changing in the customer oriented market environment. There are a wide range of factors that the consumer behavior depends upon and differs when it comes to the product, features, packaging, price, generation, status, age of the customer etc. Today's youth ranging from 18-32 years of age follows the rhythm of the fashion and taste as per the changing times. They are more inclined towards having an enhanced online shopping experience. A survey with 100 customers of online apparels in India indicated that factors such as quality, discounted options and social conformity majorly affect the purchasing behavior of the individual and their association with the product. For research purpose, the dependencies were measured by causal analysis conducted by Smart PLS 3. To summarize, this paper discusses about the drive to buy and the consequences among the youth pre and post personal consumption.